2015
DOI: 10.1080/13803395.2015.1013021
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Mild Brain Injury Atypical Symptom Scale and the Validity-10 Scale to detect symptom exaggeration in US military service members

Abstract: These findings provide strong support for the use of the Validity-10 as a tool to screen for symptom exaggeration when administering the NSI and PCL-C. The mBIAS, however, was not a reliable tool for this purpose and failed to identify the vast majority of people who exaggerated symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 45 publications
2
24
0
Order By: Relevance
“…One study replicated the initial development and validation study in servicemembers with mTBI but identified a much lower cutoff score [27]. Additionally, no studies to date have examined the Validity-10's relationship to other variables of interest in this population such as demographics, injury variables, psychiatric characteristics, VA service connection, or PVT performance.…”
Section: Introductionmentioning
confidence: 51%
See 4 more Smart Citations
“…One study replicated the initial development and validation study in servicemembers with mTBI but identified a much lower cutoff score [27]. Additionally, no studies to date have examined the Validity-10's relationship to other variables of interest in this population such as demographics, injury variables, psychiatric characteristics, VA service connection, or PVT performance.…”
Section: Introductionmentioning
confidence: 51%
“…Those scoring above 22 on the Validity-10 were identified as the SVT-fail group while those scoring 22 or below were in the SVT-pass group. Lange and colleagues identified a cutoff score of 13 or above for "symptom exaggeration" in servicemembers with a history of mTBI [27]. Thus, a cutoff score of 13 was used for the exploratory aim.…”
Section: Validity Indicatorsmentioning
confidence: 99%
See 3 more Smart Citations